Composition of White Potato Starch (Ipomea batatas L.) with Avocado Seed Starch (Persea americana Mill) and Glyserol Concentration in Edible Film - Musdar Musdar; Lukmanul Hakim; Juliani Juliani; Jailani Jailani (Universitas Serambi Mekkah, 2020)
White sweet potato starch (Ipomea batatas L.) and avocado seed starch (Parsea americana Mill) derived from local plants have the potential to be developed as agricultural products. Starch is a hydrocolloid compound as a potential local resource to be utilized. Glycerol function as an anti-freezing which is hygroscopic. This study aims to determine the ratio of white sweet potato starch with avocado seed starch and the concentration of glycerol for making edible film. This study was an experiment using a completely randimized factorial design with 2 (two) main factor consisting of a comparison of white sweet potato starch and avocado seed with 3 levels: P1 = 35%:65%., P2=50%:50%., P3=65%:35% and glycerol concentration with 3 levels: G1=1%., G2=2%., G3=3%. The best result reasearch were content of 23.03% (tratment P1G1), solubility of 55.57% (treatment P3G2)., swelling test of 9.83% (treatment P2g3)., elongation of 8.18% (treatment P3G2)